2008
DOI: 10.1080/01902140802093196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size on Slow Particle Clearance From the Bronchial Tree

Abstract: The Human Respiratory Tract Model of the International Commission on Radiological Protection assumes that a fraction of particles deposited in the bronchial tree clears slowly, this fraction decreasing with increasing particle geometric diameter. To test this assumption, volunteers inhaled 5-microm aerodynamic diameter 111In-polystyrene and 198Au-gold particles simultaneously, as a 'bolus' at the end of each breath to minimize alveolar deposition. Because of the different densities (1.05 versus 19.3 g cm3), ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…However, there is evidence supporting that some particles depositing in the tracheobronchial region are actually cleared slowly and independent on their geometric diameters (Smith et al, 2008). Therefore, the accuracy in determining regional pulmonary deposition from different particle sizes based on particle clearance should be evaluated with caution.…”
Section: Particle Deposition In the Lungsmentioning
confidence: 96%
“…However, there is evidence supporting that some particles depositing in the tracheobronchial region are actually cleared slowly and independent on their geometric diameters (Smith et al, 2008). Therefore, the accuracy in determining regional pulmonary deposition from different particle sizes based on particle clearance should be evaluated with caution.…”
Section: Particle Deposition In the Lungsmentioning
confidence: 96%
“…Bailey et al (1995) also estimated the slow-cleared fraction to decrease with increasing particle size to 0% for particles !6 mm. Additional experimental evidence from the same group (Smith et al, 2008) showed no difference in TB clearance among humans for particles with geometric sizes of 1.2 versus 5 mm, but having the same d ae (5 mm) so as to deposit similarly in the TB airways. For at least micron-sized particles, these findings do not support the particle size dependence of a slow-cleared TB fraction.…”
Section: Figurementioning
confidence: 91%
“…The assumption was that these particles would deposit only on ciliated airways (and none on alveolarized airways). More recent studies have indicated that the slow tracheobronchial clearance was most likely due to particles depositing beyond the ciliated tracheobronchial airways (Svartengren et al, 2001(Svartengren et al, , 2004Bailey et al, 2007Bailey et al, , 2008Smith et al, 2008). In addition, Philipson et al (2000) found that two particles with different physical diameters (6 and 4.5 μm), but similar aerodynamic sizes (6.2 and 6.4 μm), did not have different clearance rates when inhaled by humans.…”
Section: Slow Bronchial Clearancementioning
confidence: 99%
“…In addition, Philipson et al (2000) found that two particles with different physical diameters (6 and 4.5 μm), but similar aerodynamic sizes (6.2 and 6.4 μm), did not have different clearance rates when inhaled by humans. Smith et al (2008) performed similar studies using radiolabeled aerodynamically similar polystyrene particles (density = 1.05 g/cm 3 ) and gold particles (density = 19.3 g/cm 3 ) inhaled by human volunteers. No differences were seen in clearance rates although both particles had aerodynamic diameters of 5 μm, and they were inhaled simultaneously.…”
Section: Slow Bronchial Clearancementioning
confidence: 99%
See 1 more Smart Citation